CONTRIBUTIONS OF INSTITUTIONAL ASSESSMENT FOR THE PLANNING AND MANAGEMENT OF OTHER KNOWLEDGE - Newmann Valgueiro, Maria; Semeão Prazeres, Isaque; de Oliveira Quaresma, Daniel (Revista Gênero e Interdisciplinaridade, 2024)
This document was prepared based on the critical analysis regarding the evaluation process of learning, and the importance of institutional assessment, in the visions of the following authors: 1. ABREU JR, N., with the Article “Systems of Higher Education Evaluation Brazilian” that discerns as the Institutional Assessment, the Brazilian System of Higher Education Evaluation and academic quality; 2. BRANDALISE, MAT, and Article: “Institutional Assessment of School: concepts, contexts and practices”, which focuses on the external Institutional Assessment, Self-assessment of schools, and institutional development; and yet: 3. SOUZA, SMZL, with the Review “Institutional Assessment: elements for discussion”, which discusses the Assessment practices, the design of the school, and the importance of improving the quality of work. Our main goal in producing this paper was to perform a comparative analysis on the critical contributions of Institutional Assessment for planning and management of diverse knowledge, based on the main themes that are presented in the articles and review analyzed. In our methodology, also, we make bibliographical research of others, to enrich our theoretical foundation and preparation of this article.